UPAYA GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMPT AL-MUSYAWARAH CABANGBUNGIN - Rola Riska Sarwiyah; Abdurrohim; Taufik Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to find out the efforts of Islamic Religious Education (PAI) teachers in increasing student learning motivation, the obstacles faced by teachers, and the efforts made in overcoming these obstacles at SMPT Al-Musyawarah Cabangbungin. This study uses a qualitative approach with a descriptive type of research. Data was obtained through interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model which included data reduction, data presentation, and conclusion drawing and verification. The results of the study show that PAI teachers' efforts to increase students' motivation to learn are carried out through four main strategies, namely providing encouragement and enthusiasm for learning, providing rewards, creating a conducive, safe, and fun classroom atmosphere, and using various learning methods. In its implementation, teachers face obstacles that come from internal and external factors of students, including low willingness to learn, differences in academic ability, the influence of the social environment, peer disturbances, and less conducive classroom conditions. To overcome these obstacles, teachers provide instructions and directions in learning, recognize students' interests and potential, and use varied learning media. The findings of the study show that teachers play the role of motivators, guides, and facilitators who apply adaptive and contextual strategies to create PAI learning that is engaging, active, and in accordance with the needs of students.